A gauss-Newton regression approach to tests of nonnested hypotheses in some nonlinear econometric models - Rebelo, Efigénio (2015)
Dissertação de doutoramento, Economia, Unidade de Ciências Económicas e Empresariais, Universidade do Algarve, 1997